Elucidating the roles of acid site nature and strength in the direct conversion of levulinic acid into ethyl valerate: the case of Zr-modified beta zeolite-supported Pd catalysts. Issue 4 (31st January 2022) - Muñoz-Olasagasti, M.; Martínez-Salazar, I.; Granados, M. López; López-Aguado, C.; Iglesias, J.; Morales, G.; Mariscal, R.
Abstract : The strong Brønsted and Lewis acid sites are active in the tandem conversion of levulinic acid into ethyl valerate. The intrinsic activity of the former is more significant and the Pd/HBEA catalyst deactivation is partially reversible by calcination. Abstract : The effects of the nature and strength of surface acid sites on the properties of the catalyst used for the one-pot conversion of levulinic acid to valeric biofuels have been investigated. The acid supports were prepared from a commercial beta zeolite (HBEA) modified by partial substitution of Al by Zr atoms. This procedure enables changes in the nature and strength of the acidic sites of the starting zeolite. A constant amount of Pd (2 wt%) was incorporated on these acid supports by the incipient wetness impregnation method. These catalysts were tested in liquid phase reactions and the Pd/HBEA catalyst showed the best catalytic performance, achieving an 80% yield of valeric biofuel after 2 h of the reaction. The fresh catalysts were characterized by DRIFT spectroscopy using pyridine, CD3 CN, and CO as probe molecules and by XRD to explain the differences in catalytic performance. The presence of strong Brønsted acid sites (BAS) was shown to be critical for reaching high ethyl valerate yields since the differences in catalytic behavior and the concentration of these acid sites parallel each other. Up to three types of Lewis acid sites (LAS) of different strengths were also identified. These LAS have also been shown to be active, although their intrinsic activities decrease as they are weaker. Reutilization tests of the Pd/HBEA catalyst were also carried out and mild deactivation was observed. The spent catalyst underwent a simple calcination treatment at 773 K and this was adequate for the recovery of the surface acidity, but the reducibility of the Pd species was affected. This prevented complete recovery of catalytic activity.